DFT study of the reaction between VO2+ and C2H6 - Gracia, L.; Andres, J.; Safont, V. S.; Beltran, A. (Amer Chemical Soc, 2004)
The molecular mechanisms of the reaction VO2+ ((1)A(1)/(3)A'') + C2H6 ((1)A(g)) to yield V(OH)(2)(+) ((1)Sigma(+)/(3)Sigma(-)) + C2H4 ((1)A(g)) and/or VO+ ((1)Delta/(3)Sigma) + H2O ((1)A(1)) + C2H4 (Ag-1) have been investigated with density functional theory (DFT) at the B3LYP/6-311G(2d,p) level. Calculations including geometry optimization, vibrational analysis, and Gibbs free energy for the stationary points on the reactive potential energy surfaces at both the singlet (s) and first excited triplet (t) electronic states have been carried out. The most thermodynamically and kinetically favorable pathway is the formation of t-V(OH)(2)(+) + C2H4 along a four-step molecular mechanism (insertion, two consecutive hydrogen transfers, and elimination). A crossing point between s and t electronic states has been characterized. A comparison with previous works on VO2+ + C2H4 (Gracia et al. J. Phys. Chem. A 2003, 107, 3107-3120) and VO2+ + C3H8 (Engeser et al. Organometallics 2003, 22, 3933-3943) reactions allows us a rationalization of the different reactivity patterns. The catalytic role of water molecules in the tautomerization process between hydrated oxide cation, VO(H2O)(+,) and dihydroxide cation, V(OH)(2)(+), is achieved by a water-assisted mechanism.